Design of novel iron compounds as potential therapeutic agents against tuberculosis - Belen Tarallo, M.; Urquiola, Carolina; Monge, Antonio; Parajon Costa, Beatriz; Ribeiro, Ronny R.; Costa-Filho, Antonio J.; Mercader, Roberto C.; Pavan, Fernando Rogério [UNESP]; Leite, Clarice Queico Fujimura [UNESP]; Torre, Maria H.; Gambino, Dinorah (Elsevier B.V., 2010)
In the search for new therapeutic tools against tuberculosis two novel iron complexes, [Fe(L-H)3], with 3-aminoquinoxaline-2-carbonitrile N(1),N(4)-dioxide derivatives (L) as ligands, were synthesized, characterized by a combination of techniques, and in vitro evaluated. Results were compared with those previously reported for two analogous iron complexes of other ligands of the same family of quinoxaline derivatives. In addition, the complexes were studied by cyclic voltammetry and EPR spectroscopy. Cyclic voltammograms of the iron compounds showed several cathodic processes which were attributed to the reduction of the metal center (Fe(III)/Fe(II)) and the coordinated ligand. EPR signals were characteristic of magnetically isolated high-spin Fe(III) in a rhombic environment and arise from transitions between m(s) = +/- 1/2 (geff-9) or m(s) = +/- 3/2 (g(eff)similar to 4.3) states. Mossbauer experiments showed hyperfine parameters that are typical of high-spin Fe(III) ions in a not too distorted environment. The novel complexes showed in vitro growth inhibitory activity on Mycobacterium tuberculosis H(37)Rv (ATCC 27294), together with very low unspecific cytotoxicity on eukaryotic cells (cultured murine cell line J774). Both complexes showed higher inhibitory effects on M. tuberculosis than the "second-line" therapeutic drugs. (C) 2010 Elsevier B.V. All rights reserved.
Keywords: Tuberculosis; Iron; Quinoxaline N(1),N(4)-dioxides; Mycobacterium tuberculosis